The Coherence of the European Union Marine Natura 2000 Network for Wide-Ranging Charismatic Species: A Mediterranean Case Study - Fortuna, Caterina Maria; Cañadas, Ana; Holcer, Draško; Brecciaroli, Benedetta; Donovan, Gregory P.; Lazar, Bojan; Mo, Giulia; Tunesi, Leonardo; Mackelworth, Peter C. (Frontiers in Marine Science, 2018)
The Natura 2000 (N2k) network is an important site-based protection tool for the protection of biodiversity in Europe. However, for highly mobile and adaptable marine species, such a tool might not be the most effective way to achieve conservation objectives, unless this includes a broader consideration of the direct threats to these species throughout their range. Considering that the N2k network requires that a ‘significant proportion’ of 60% of the population be under protection, this creates a challenge for the conservation of these wide-ranging species. This paper reviews the efficacy of the N2k network as it is presently implemented within the Adriatic Sea for the conservation of two highly mobile marine species - the common bottlenose dolphin and the loggerhead turtle. In particular, it considers the appropriateness of the current Sites of Community Importance (SCIs) in the region and the relevance of the existing marine N2k network for the conservation of these species. It provides new insights on the approach used to evaluate SCI designations highlighting important weaknesses in the system, including threat identification after SCI designation, and the relevance of SCI size in relation to management commitments. Data from two basin-wide aerial surveys were used to define areas of relative high density of these species, in comparison to other areas in the basin. Given the ambitious 60% conservation target of the N2k network, analysis shows that site-based protection tools are unlikely to be sufficient to protect a ‘significant proportion’ of either species, unless very large areas are designated as SCIs. However, given that the main threats known to affect these species in this region (i.e. fishery bycatch and seismic surveys) are present throughout the basin, these large SCIs would still have limited conservation success without implementing other wide-scale mitigation measures. For these two species, the Member States and the European Union authorities should give higher priority to the implementation of another pillar of the Habitats Directive, mitigating accidental catches in fishing gear and other human-induced mortalities. This should take into consideration the full effects of these mortalities on the populations of these two species through regular transboundary monitoring programs.